Islamic Social Entrepreneurship Model Of Business Women In Pandemic Era: Evidence From Indonesia - Nurul Asfiah; Ratya Shafira Arifiani; Rizki Febriani; Yeyen Pratika (Jurnal Reviu Akuntansi dan Keuangan, 2022)
The pandemic has caused the economic sector to change, especially for businesses in the social sector. This study aims to create a business model with the concept of Islamic Social Entrepreneurship for entrepreneurial women in the pandemic Covid-19 era. This study is based on the case of Micro and Small Enterprises (SMEs) belonging to the "Association of Women Entrepreneurs of ‘Aisyiyah (IPAS)," where ‘Aisyiyah’s organization acts as a social agent. The world is currently experiencing a crisis caused by a pandemic Covid-19, resulting in a significant downturn in the Micro, Small, Medium Enterprise (MSME) sector. This research is a qualitative study and focuses on Islamic social entrepreneurship in the pandemic era. Data analysis was performed simultaneously, recursively, and dynamically, where conceptualization, categorization, and description were carried out together. This study indicates that women can be independent and improve their quality of life with Islamic social entrepreneurship following the values developed.